1987
DOI: 10.1111/j.1559-1816.1987.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Clothing and Dyad Sex Composition on Perceptions of Sexual Intent: Do Women and Men Evaluate These Cues Differently1

Abstract: The effects of clothing revealingness and dyad‐sex composition on perceptions of male‐ and female‐stimulus persons' sexuality were examined. Based on Abbey's (1982) findings, we hypothesized that men would attribute more sexuality to both male and female targets than women would. Furthermore, we predicted that the difference between men's and women's sexuality ratings would be most divergent when a male‐female dyad was presented and when the female stimulus person wore revealing clothing. A laboratory study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
98
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 13 publications
9
98
3
Order By: Relevance
“…On the contrary, there is evidence that women risk backlash for self-sexualization. For example, women are judged more negatively by both genders when wearing provocative (e.g., low-cut blouse, high-heeled shoes) compared with conservative clothing (e.g., buttoned-up blouse, flat shoes; Abbey, Cozzarelli, McLaughlin, & Harnish, 1987;Cahoon & Edmonds, 1989), and they are perceived as more qualified for secretarial rather than managerial roles (Glick et al, 2005;Wookey, Graves, & Butler, 2009). How might backlash against self-sexualizing women be explained?…”
Section: Empowered Self-sexualizationmentioning
confidence: 99%
“…On the contrary, there is evidence that women risk backlash for self-sexualization. For example, women are judged more negatively by both genders when wearing provocative (e.g., low-cut blouse, high-heeled shoes) compared with conservative clothing (e.g., buttoned-up blouse, flat shoes; Abbey, Cozzarelli, McLaughlin, & Harnish, 1987;Cahoon & Edmonds, 1989), and they are perceived as more qualified for secretarial rather than managerial roles (Glick et al, 2005;Wookey, Graves, & Butler, 2009). How might backlash against self-sexualizing women be explained?…”
Section: Empowered Self-sexualizationmentioning
confidence: 99%
“…That must mean she's sexually attracted to me'; 'She's willing to have a nightcap in my apartment. That must mean she's really sexually attracted to me ' Abbey et al, 1987).…”
mentioning
confidence: 98%
“…A study of college students' perceptions of sexuality based on revealing attire showed that females were rated as more fl irtatious, sexy, promiscuous, and seductive when wearing revealing compared with non-revealing clothing (Abbey, Cozzarelli, McLaughlin, & Harnish, 1987). Students rated the likelihood that members of male-female dyads were romantically involved and sexually attracted to each other higher when the female wore revealing as opposed to non-revealing clothes.…”
mentioning
confidence: 99%
“…Consistent with the idea that the sexy confederate from Study 1 was in fact viewed as a sexual rival, we hypothesized that women would be less willing to introduce her to their current or future boyfriend(s), or have their current or future boyfriend(s) spend time alone with her than the attractive conservative confederate or the sexy-fat confederate. We also hypothesized that compared to the conservatively dressed confederate, women would not want to introduce their partner or allow him to spend time with the sexy-fat woman because her sexy clothing would be perceived as an indicator of sexual availability and hence would be threatening 1 [Abbey et al, 1987].…”
mentioning
confidence: 99%